2007
DOI: 10.1128/aem.02751-06
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methods for Genetic Transformation of Natural Bacillus subtilis Isolates Used To Study the Regulation of the Mycosubtilin and Surfactin Synthetases

Abstract: Natural isolates of Bacillus subtilis are often difficult to transform due to their low genetic competence levels. Here we describe two methods that stimulate natural transformation. The first method uses plasmid pGSP12, which expresses the competence transcription factor ComK and stimulates competence development about 100-fold. The second method stimulates Campbell-type recombination of DNA ligation mixtures in B. subtilis by the addition of polyethylene glycol. We employed these novel methods to study the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 52 publications
1
53
0
Order By: Relevance
“…In B. subtilis, overexpression of comK allows for genetic access of non-competent wild isolates (Duitman et al 2007;Nijland et al 2010). Artificially induced competence was successfully applied for close relatives of B. subtilis as well: in B. licheniformis MW3.1, overexpression of the homologous comK yielded up to 2.97×10 5 transformants per microgram of chromosomal DNA-an efficiency that allows for direct gene knock outs and even conditional knock outs of essential genes (Hoffmann et al 2010).…”
Section: Artificial Induction Of Genetic Competencementioning
confidence: 99%
“…In B. subtilis, overexpression of comK allows for genetic access of non-competent wild isolates (Duitman et al 2007;Nijland et al 2010). Artificially induced competence was successfully applied for close relatives of B. subtilis as well: in B. licheniformis MW3.1, overexpression of the homologous comK yielded up to 2.97×10 5 transformants per microgram of chromosomal DNA-an efficiency that allows for direct gene knock outs and even conditional knock outs of essential genes (Hoffmann et al 2010).…”
Section: Artificial Induction Of Genetic Competencementioning
confidence: 99%
“…Its expression is highest at the end of logarithmic phase (Tsuge et al 2001b). Duitman et al (2007) have shown recently that mycosubtilin synthetase expression is under the influence of a regulatory cascade depending on AbrB, one of the main transition state regulators in B. Fig.…”
Section: Quorum Sensing and Surfactin Effluxmentioning
confidence: 99%
“…Performed on surfactin synthetase, the same promoter exchange did not allow the improvement of the surfactin production (Coutte et al 2010a). The native promoter P srf of Bacillus subtilis 168 is considered very efficient, frequently allowing the concentration of surfactin in the culture supernatant to be higher than 1 g l À1 (Duitman et al 2007). The horizontal transfer of iturin operon in Bacillus subtilis 168 together with a functional sfp gene and the pleiotropic regulator degQ allowed conversion of this strain to an efficient iturin producer (Tsuge et al 2005).…”
Section: Directed Biosynthesis and Molecular Optimisationmentioning
confidence: 99%
“…The chemical principles for the biosynthesis of iturin-like compounds are also largely characterized (12,44). In contrast, little is known about the regulatory mechanisms that control the expression of the iturin-like lipopeptides (13).…”
mentioning
confidence: 99%